A Universal Pick‐and‐Place Assembly for Nanowires. Issue 38 (8th August 2022) - Ali, Utku Emre; Yang, He; Khayrudinov, Vladislav; Modi, Gaurav; Cheng, Zengguang; Agarwal, Ritesh; Lipsanen, Harri; Bhaskaran, Harish
Abstract: With the introduction of techniques to grow highly functional nanowires of exotic materials and demonstrations of their potential in new applications, techniques for depositing nanowires on functional platforms have been an area of active interest. However, difficulties in handling individual nanowires with high accuracy and reliability have so far been a limiting factor in large‐scale integration of high‐quality nanowires. Here, a technique is demonstrated to transfer single nanowires reliably on virtually any platform, under ambient conditions. Functional nanowires of InP, AlGaAs, and GeTe on various patterned structures such as electrodes, nanophotonic devices, and even ultrathin transmission electron microscopy (TEM) membranes are transferred. It is shown that the versatility of this technique further enables to perform on‐chip nano‐optomechanical measurements of an InP nanowire for the first time via evanescent field coupling. Thus, this technique facilitates effortless integration of single nanowires into applications that were previously seen as cumbersome or even impractical, spanning a wide range from TEM studies to in situ electrical, optical, and mechanical characterization. Abstract : Despite their fascinating properties, the integration of nanowires at the device level remains challenging. Here, the authors introduce novel nanoscale tools to manipulate single nanowires and place them onto predetermined locations within <1 µm accuracy. This is the first instance of a deterministic nanowire integration technique, with the imminent promise of mass‐produced nanowire devices.